The Effect of Corporate Social Responsibility on Investment Decisions: The Mediating Role of ESG Score on Banking Companies in Indonesia - Fadhia, Husnuzzahra; Rahma Elika, Dirda; Dian Pratiwi, Permata (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) on investment decisions in Indonesia's banking sector, considering the role of the ESG (Environmental, Social, Governance) Score as a mediating variable. A quantitative approach is used, involving eight banking companies listed on the Indonesia Stock Exchange (IDX) and included in the IDX ESG Leaders index from 2019 to 2023, with a total sample of 40 research samples. The research findings indicate that CSR disclosure does not have a direct effect on investment decisions. However, ESG mediation significantly impacts CSR and investment decisions, and ESG is associated with EPS. These results suggest that ESG can act as a bridge for CSR in investment decision-making.